COVID-19 Lockdown effect: surge of alcohol withdrawal cases in emergency department (Journal of Patan Academy of Health Sciences, 2020)
States around the world has imposed lockdown to mitigate with COVID-19. This has caused unavailability of commodities including liquor. After lockdown, we observed increase in the number alcohol withdrawal cases in Emergency department of Patan hospital, Nepal. In contrast, during post-earthquake period in 2015 there was increase in number of alcohol intoxication cases. During pandemic time, along with managing COVID-19 cases, other alarming public health concerns should be noticed and necessary health support needs to be planned.